2019
DOI: 10.1111/vde.12741
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of orally administered fluralaner for treatment of scabies in six free‐ranging raccoon dogs (Nyctereutes procyonoides)

Abstract: Background Sarcoptic mange in free‐ranging raccoon dogs (Nyctereutes procyonoides) caused by Sarcoptes scabiei is a widespread zoonotic disease that causes severe skin lesions with significant morbidity and mortality. Fluralaner is a member of the isoxazoline chemical class and is an acaricide and insecticide widely used in flea, tick and mite infections of dogs (Canis lupus familiaris). Objective To evaluate the clinical efficacy of orally administered fluralaner in free‐ranging raccoon dogs naturally infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The current work revealed no apparent side effects in the FLR-treated animals. Similarly, Hyun et al ( 2019 ) reported that no side effects were noticed following FLR administration, apart from a single bout of diarrhea that was observed in one raccoon dog that received a higher dose of FLR (52.3 mg/kg body weight). Interestingly, FLR was also demonstrated to be safe and well-tolerated in a preliminary study in wombats using a high dosage of 85 mg/kg (Wilkinson et al 2021 ).…”
Section: Discussionmentioning
confidence: 84%
“…The current work revealed no apparent side effects in the FLR-treated animals. Similarly, Hyun et al ( 2019 ) reported that no side effects were noticed following FLR administration, apart from a single bout of diarrhea that was observed in one raccoon dog that received a higher dose of FLR (52.3 mg/kg body weight). Interestingly, FLR was also demonstrated to be safe and well-tolerated in a preliminary study in wombats using a high dosage of 85 mg/kg (Wilkinson et al 2021 ).…”
Section: Discussionmentioning
confidence: 84%
“…Since the expansion of the distribution of long-tailed gorals in this country often overlaps with other host species such as wild raccoon dogs (Nyctereutes procyonoides), wild boars (Sus scrofa), and feral dogs, the possibility of cross-infection with S. scabiei cannot be ruled out. For instance, wild raccoon dogs and freeranging stray dogs have previously been diagnosed to have scabies in Korea [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity reactions of wild raccoon dogs and feral dogs to S. scabiei was commonly reported in Korea. It is known that the numbers and spaces of these dwelling animals are also expanding [ 10 , 11 ]. In Japan, epizootics of sarcoptic mange in raccoon dogs might be related to the high density of the host population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with sarolaner, the data of the fluralaner study suggest a more rapid resolution of canine sarcoptic mange by achieving 100% efficacy in a month, while sarolaner required 2 months to reach clinical cure with a monthly dosing interval (Taenzler et al, 2016). In addition, a study of six racoon dogs revealed 100% negative skin scraping in 7 days following a single oral dose of fluralaner; parasitological and clinical cure maintained up to 21 days (Hyun et al, 2019). Afoxolaner, given orally on days 0, 14, 28, and 56, appeared to exhibit a slower speed of killing against Sarcoptes scabiei in dogs, as it necessitated one more month than sarolaner to obtain 99% efficacy (Beugnet, de Vos, et al, 2016).…”
Section: Ectoparasiticidal Effectsmentioning
confidence: 99%
“…As with the treatment of demodicosis, these treatment modalities can be risky and cumbersome. All isoxazolines except lotilaner have been studied extensively for the treatment of canine sarcoptic mange (Becskei, De Bock, Illambas, Cherni, et al, 2016; Beugnet, de Vos, et al, 2016; Hyun et al, 2019; Taenzler et al, 2016). Sarolaner has been demonstrated to be extremely effective within 14 days of dose against nymphs, larvae, and adults, with over 99% efficacy compared with the control groups by week 2 and 100% reduction by week 4 (Becskei, De Bock, Illambas, Cherni, et al, 2016).…”
Section: Ectoparasiticidal Effectsmentioning
confidence: 99%